Does Depreciation of Currency Always Invite Debt Trap? - Fujita, Yasunori (Archives of Business Research, 2022)
In the present paper, motivated by the debate over the causes of the debt trap Sri Lanka fell into and by extending Padoan et al (2012) that focused on a country with domestic debt only, we construct a theoretical model that incorporates the foreign debt to investigate the condition where the debt trap is avoided. The results we obtain are as follows. (1) Country falls into the debt trap no matter what the exchange rate is if the growth rate of the GDP without foreign debt is low, the government expenditure is not effective, increase in the foreign debt is smaller the foreign interest rate is high. (2) Depreciation of the currency is necessary for the country to avoid the debt trap if the growth rate of the GDP without foreign debt is high, the government expenditure is effective, increase in the foreign debt is large or the foreign interest rate is low. (3) The more the foreign debt influences the GDP, the weaker its currency should be in order to avoid the debt trap.